A Straightforward Philosophical Thought About Virtual Reality and Environmentalism - Wood, Brent (UnderCurrents: Journal of Critical Environmental Studies, 1993)
The world, not the planet, is becoming virtual. Our idea of ’the planet’ is already a virtual one, as the currently multiplying photos of the globe from space wordlessly attest. When we try to conceive of a ’global system’ of any kind, our imaginations prove inadequate to the task. Hence the sublime experience aroused when we attempt. to contemplate our earth in its entirety in one of our more peaceful, less procedural moments, as when a young adult cries at the beach on a summer evening over the fate of humanity. [...]